AKULTURASI PEMIKIRAN DAN SAINS YUNANI DALAM DUNIA ISLAM - Ghazali Munir (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
Acculturation in the field of culture and ideas between one group with another group, can’t be avoided when there are contacts or interactions between them. Interaction, either peacefully or by occupation and even war. In this case, it occurred among the nations of the world, especially the Greeks and Arabs, and it seemed/looked the wealth of Greek philosophy and science and its role in the Arab calips (Muslim) in the development of philosophy and science.